MAC2 is a long‐lasting marker of peripheral cell infiltrates into the mouse CNS after bone marrow transplantation and coronavirus infection. Issue 5 (13th January 2022) - Hohsfield, Lindsay A.; Tsourmas, Kate I.; Ghorbanian, Yasamine; Syage, Amber R.; Jin Kim, Sung; Cheng, Yuting; Furman, Susana; Inlay, Matthew A.; Lane, Thomas E.; Green, Kim N.
Abstract: Microglia are the primary resident myeloid cells of the brain responsible for maintaining homeostasis and protecting the central nervous system (CNS) from damage and infection. Monocytes and monocyte‐derived macrophages arising from the periphery have also been implicated in CNS pathologies, however, distinguishing between different myeloid cell populations in the CNS has been difficult. Here, we set out to develop a reliable histological marker that can assess distinct myeloid cell heterogeneity and functional contributions, particularly in the context of disease and/or neuroinflammation. scRNAseq from brains of mice infected with the neurotropic JHM strain of the mouse hepatitis virus (JHMV), a mouse coronavirus, revealed that Lgals3 is highly upregulated in monocyte and macrophage populations, but not in microglia. Subsequent immunostaining for galectin‐3 (encoded by Lgals3 ), also referred to as MAC2, highlighted the high expression levels of MAC2 protein in infiltrating myeloid cells in JHMV‐infected and bone marrow (BM) chimeric mice, in stark contrast to microglia, which expressed little to no staining in these models. Expression of MAC2 was found even 6–10 months following BM‐derived cell infiltration into the CNS. We also demonstrate that MAC2 is not a specific label for plaque‐associated microglia in the 5xFAD mouse model, but only appears in a distinct subset of these cells in the presence of JHMV infection or during aging. Our data suggest that MAC2 can serve as a reliable and long‐lasting histological marker for monocyte/macrophages in the brain, identifying an accessible approach to distinguishing resident microglia from infiltrating cells in the CNS under certain conditions. Main Points: Lgals3 is upregulated in monocyte/macrophage populations. Galectin‐3/MAC2 labels bone marrow‐derived monocytes 6–10 months following cell infiltration into the CNS, but not microglia. MAC2 is not a specific marker for plaque‐associated microglia.